Luce [videorecording (DVD)] - Onah, Julius, 1983-; Watts, Naomi, 1968-; Spencer, Octavia; Roth, Tim; Harrison, Kelvin, Jr., 1994-; Lee, J. C. (Justin C.) (Universal Pictures Home Entertainment, 2019)
Garnering recognition for his stellar athletic abilities and intellectual accomplishments "Luce" follows the titular characters struggle of maintaining his integrity while dealing with the circumstances of his background. Adopted from a war-torn country just ten years prior, Luce becomes the very essence of what many consider to be the American Dream. However, all changes when his teacher encounters a shocking revelation upon examining the contents of Luce's locker. Luce is then charged with fighting to maintain his integrity and reputation, as everyone around him begins to question his true character and motives.